2021
DOI: 10.1021/acs.inorgchem.1c02922
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-Assisted Assembly of Pearl-Chain-Like Cyanide-Bridged Single-Chain Magnets

Abstract: The introduction of Keggin-type POMs of [PMo12O40]3– or [SiW12O40]4– as counteranions into the FeIII–MII cyanometalate system afforded three chain complexes: [(Tp*)­Fe­(CN)3­Ni­(DMF)4]2­{[(Tp*)­Fe­(CN)3­Ni­(DMF)3(H2O)]2­Ni­(DMF)4}­[PMo12O40]2·14DMF (1, Tp*= hydridotris­(3,5-dimethylpyrazol-1-yl)­borate) and {[(Tp*)­Fe­(CN)3­M­(DMF)3­(H2O)]2­M­(DMF)4}­[SiW12O40]·3DMF (2, M = NiII; 3, M = CoII). Complex 1 contains both discrete cationic [Fe2Ni2]2+ squares and less-studied {Fe2Ni3} n pearl chains, namely 3,2-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…85 On the other hand, the orientations of the pseudo- C 3 rotation axes on the iron sites (along the B⋯Fe direction) may also function as structural markers for the anisotropic exchange interactions, where parallel orientations generally lead to a favorable alignment of the magnetic moments. 86 As shown in Fig. S19,† the angle between adjacent pseudo- C 3 axes ( α ) for the Fe III sites in compound 1 (45.7(3)°) was smaller than that in 2 (up to 55.1(7)°).…”
Section: Resultsmentioning
confidence: 92%
“…85 On the other hand, the orientations of the pseudo- C 3 rotation axes on the iron sites (along the B⋯Fe direction) may also function as structural markers for the anisotropic exchange interactions, where parallel orientations generally lead to a favorable alignment of the magnetic moments. 86 As shown in Fig. S19,† the angle between adjacent pseudo- C 3 axes ( α ) for the Fe III sites in compound 1 (45.7(3)°) was smaller than that in 2 (up to 55.1(7)°).…”
Section: Resultsmentioning
confidence: 92%
“…Polyoxometalates (POMs) are well-defined early transition metal-oxygen clusters, which have remarkable performance in reserving protons and electrons [8][9][10] and can be excellent candidates for the development of OER catalysts due to their molecular nature, structural diversity, redox properties, and so on. [11][12][13][14][15][16][17][18] Recent studies have shown that some research teams are exploring polyacid-based metal-organic skeleton compounds using a combination of POM-MOF structures as efficient electrocatalysts. [19][20][21][22] In fact, controversy has arisen on the question of whether POMs are used as true electrocatalysts or only as pre-catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Cyanide-bridged transition metal compounds have drawn continuous attention from researchers worldwide due to their unique properties that allow for the construction of functional magnetic materials such as single-molecule magnets (SMMs), 1 single-chain magnets (SCMs), 1 a ,2 spin crossover (SCO) compounds, 3 and metal-to-metal electron transfer (MMET) compounds. 4 One particularly interesting class of these compounds is heterometallic complexes like Fe/Co ones, which exhibit the intriguing metal-to-metal electron-transfer-coupled spin transition (ETCST) between the diamagnetic {Fe II LS (μ-CN)Co III LS } state and paramagnetic {Fe III LS (μ-CN)Co II HS } state (LS = low spin and HS = high spin).…”
Section: Introductionmentioning
confidence: 99%